Variational analysis of flat-top solitons in Bose–Einstein condensates - B. B., Baizakov; A., Bouketir; Messikh, Azeddin; Umarov, Bakhram (World Scientific Publishing Company, 2011)
Static and dynamic properties of matter-wave solitons in dense Bose–Einstein conden- sates, where three-body interactions play a significant role, have been studied by a variational approximation (VA) and numerical simulations. For experimentally relevant parameters, matter-wave solitons may acquire a flat-top shape, which suggests employing a super-Gaussian trial function for VA. Comparison of the soliton profiles, predicted by VA and those found from numerical solution of the governing Gross–Pitaevskii equation shows good agreement, thereby validating the proposed approach.